Ultrafast single-shot amplitude swing pulse measurement - Cristian Barbero; Íñigo J Sola; Benjamín Alonso (JPhys Photonics)
Single-shot characterization techniques are crucial when handling shot-to-shot pulse-shape fluctuations (e.g. unstable laser systems, with high-power, or low repetition rate) because scanning configurations cannot measure single pulses. The demand for simple setups that can easily be adapted to a wide variety of experimental conditions is continuously rising. In this work, we propose a single-shot implementation of amplitude swing that maintains the compactness, versatility, and robustness of its scanning counterparts. First, we theoretically study the proposed implementation, based on a pair of uniaxial wedges. Then, we present the retrieval ptychographic algorithm. Finally, we experimentally demonstrate the setup by comparing the single-shot and scanning traces, along with their retrieved pulses. In sum, we provide the ultrafast science community with a simple and versatile setup capable of measuring single laser pulses, meeting the growing demand to characterize fluctuating pulse trains.